A new lactam alkaloid from Portulaca oleracea L. and its cytotoxity. Issue 13 (3rd July 2018) - Zhao, Chengcheng; Ying, Zheming; Tao, Xiaojun; Jiang, Mingyue; Ying, Xixiang; Yang, Guanlin
Abstract: A new lactam alkaloid named oleraciamide D (1 ), indentified as (5 R )-4-(3-methoxy-4-hydroxyphenyl)-5-(4-hydroxyphenyl)-5, 6-dihydropyridin-2(1 H )-one, together with five known compounds, indole-3-aldehyde (2 ), portulacatone (3 ), N - trans -feruloyloctopamine (4 ), N - trans -feruloyl-3′-O-methyldopamine (5 ) and N - trans -feruloyltyramine (6 ) were isolated from Potulaca oleracea L. Among them, indole-3-aldehyde (2 ) was isolated from the medicine for the first time. The structure of the new alkaloid was elucidated via UHPLC-ESI-Q-TOF/MS, 1D NMR and 2D NMR. The five known compounds were established by comparing the 1 H-NMR and 13 C NMR with the reported literature. Oleraciamide D (1 ) showed cytotoxicity against SH-SY5Y cells when concentration at 50 uM by CCK-8 method. Abstract :